Homeopathy in the Age of Antimicrobial Resistance: Is It a Viable Treatment for Upper Respiratory Tract Infections? - Fixsen, Alison (Homeopathy, 2018)
Background Acute upper respiratory tract infections (URTIs) and their complications are the most frequent cause of antibiotic prescribing in primary care. With multi-resistant organisms proliferating, appropriate alternative treatments to these conditions are urgently required. Homeopathy presents one solution; however, there are many methods of homeopathic prescribing. This review of the literature considers firstly whether homeopathy offers a viable alternative therapeutic solution for acute URTIs and their complications, and secondly how such homeopathic intervention might take place.Method Critical review of post 1994 clinical studies featuring homeopathic treatment of acute URTIs and their complications. Study design, treatment intervention, cohort group, measurement and outcome were considered. Discussion focused on the extent to which homeopathy is used to treat URTIs, rate of improvement and tolerability of the treatment, complications of URTIs, prophylactic and long-term effects, and the use of combination versus single homeopathic remedies.Results Multiple peer-reviewed studies were found in which homeopathy had been used to treat URTIs and associated symptoms (cough, pharyngitis, tonsillitis, otitis media, acute sinusitis, etc.). Nine randomised controlled trials (RCTs) and 8 observational/cohort studies were analysed, 7 of which were paediatric studies. Seven RCTs used combination remedies with multiple constituents. Results for homeopathy treatment were positive overall, with faster resolution, reduced use of antibiotics and possible prophylactic and longer-term benefits.Conclusions Variations in size, location, cohort and outcome measures make comparisons and generalisations concerning homeopathic clinical trials for URTIs problematic. Nevertheless, study findings suggest at least equivalence between homeopathy and conventional treatment for uncomplicated URTI cases, with fewer adverse events and potentially broader therapeutic outcomes. The use of non-individualised homeopathic compounds tailored for the paediatric population merits further investigation, including through cohort studies. In the light of antimicrobial resistance, homeopathy offers alternative strategies for minor infections and possible prevention of recurring URTIs.
Keywords: homeopathy; antimicrobial resistance; upper respiratory tract infections; clinical studies; combination remedies